Verdad y metáfora: una aproximación pragmática - Eduardo Fermandois (Crítica)
What does the (possible) truth of a metaphor consist in? The first part of this paper is a critical analysis of the following model: A metaphorical statement is true if and only if it somehow leads to the recognition of literal truths. This model of metaphorical truth as indirect literal truth is not utterly inadequate, but it fails to account for certain central features of the metaphorical: the openness of the interpretation of living metaphors, the phenomenon of the so called metaphorical chains (or nets), the non-propositional aspects of many metaphors, and the active, creative role of the interpreter. In the second part I develop an alternative model, based on: a) a pragmatist methodology with respect to the truth-issue in general (truth without representation), b) Goodman's concept of rightness, c) the difference between saying and showing, and d) the idea, that a good metaphor creates a new context which not only allows us to say something new concerning the topic in question, but which allows us to treat the topic in a new manner.